Review of Statcom EPC Project Schedule and Optimization of the Overall Timeline - Rafique, Asad (My University, 2025)
The thesis explores the optimization of Statcom project schedule within the context of Engineering, Procurement, and Construction projects, with a strong emphasis on identifying the bottle necks, the application of the Critical Path Method and fast-tracking techniques for efficient project management. EPC projects are known for their complexity due to the integration and interface of multiple disciplines, tight timelines, high cost implications, and the critical need for accurate scheduling. To make sure that projects are completed within contractual time, without compromising quality or exceeding the budget, is a major challenge for project managers, especially in large-scale infrastructure projects. The research aims to investigate the current Statcom project schedule, identify the bottlenecks, how CPM can be effectively utilized to identify critical tasks that directly impact project timelines, as well as strategies for mitigating potential delays. The thesis also examines the fast-tracking technique, where multiple tasks are performed simultaneously instead of sequentially, to reduce overall project duration. This is particularly crucial for industries such as energy infrastructure, where delays can significantly impact project costs and EPC companies’ reputation. As a key part of this study, a Statcom project has been selected as a case study to provide real-world insight into the scheduling challenges faced in these complex projects and how optimization methods can be applied to enhance project outcomes. The research adopts a multi-method approach, incorporating theoretical frameworks, case study analysis, and qualitative interviews with managers and industry experts. The case study of the Statcom project serves as a practical reference to identify the bottle necks and use of CPM and fast-tracking techniques in improving project scheduling and performance. In-depth interviews managers reveal challenges in six major engineering phases which are system design, electromechanical design, hardware design, software design, procurement and installation phase. Ultimately, this thesis makes a significant contribution to the understanding of schedule optimization, offering practical insights for the ongoing Statcom project. By reducing project timelines, improving critical path identification, and managing bottlenecks through improved scheduling methods, the study provides a valuable roadmap for enhancing project efficiency in Electrical industry. The findings are intended to guide industry practitioners, helping them implement the best practices for managing complex projects under stringent timelines and resource constraints. Thus, the research offers actionable strategies for future projects, ensuring the study’s lasting relevance in project management.
Keywords: project management; projects; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management